Photorepair of Either CPD or 6-4PP DNA Lesions in Basal Keratinocytes Attenuates Ultraviolet-Induced Skin Effects in Nucleotide Excision Repair Deficient Mice - Kajitani, Gustavo S.; Quayle, Carolina; Garcia, Camila C. M.; Fotoran, Wesley L.; dos Santos, Juliana F. R.; van der Horst, Gijsbertus T. J.; Hoeijmakers, Jan H. J.; Menck, Carlos F. M. (Frontiers in Immunology, 2022)
Ultraviolet (UV) radiation is one of the most genotoxic, universal agents present in the environment. UVB (280-315 nm) radiation directly damages DNA, producing cyclobutane pyrimidine dimers (CPDs) and pyrimidine 6-4 pyrimidone photoproducts (6-4PPs). These photolesions interfere with essential cellular processes by blocking transcription and replication polymerases, and may induce skin inflammation, hyperplasia and cell death eventually contributing to skin aging, effects mediated mainly by keratinocytes. Additionally, these lesions may also induce mutations and thereby cause skin cancer. Photolesions are repaired by the Nucleotide Excision Repair (NER) pathway, responsible for repairing bulky DNA lesions. Both types of photolesions can also be repaired by distinct (CPD- or 6-4PP-) photolyases, enzymes that specifically repair their respective photolesion by directly splitting each dimer through a light-dependent process termed photoreactivation. However, as photolyases are absent in placental mammals, these organisms depend solely on NER for the repair of DNA UV lesions. However, the individual contribution of each UV dimer in the skin effects, as well as the role of keratinocytes has remained elusive. In this study, we show that in NER-deficient mice, the transgenic expression and photorepair of CPD-photolyase in basal keratinocytes completely inhibited UVB-induced epidermal thickness and cell proliferation. On the other hand, photorepair by 6-4PP-photolyase in keratinocytes reduced but did not abrogate these UV-induced effects. The photolyase mediated removal of either CPDs or 6-4PPs from basal keratinocytes in the skin also reduced UVB-induced apoptosis, ICAM-1 expression, and myeloperoxidase activation. These findings indicate that, in NER-deficient rodents, both types of photolesions have causal roles in UVB-induced epidermal cell proliferation, hyperplasia, cell death and inflammation. Furthermore, these findings also support the notion that basal keratinocytes, instead of other skin cells, are the major cellular mediators of these UVB-induced effects.